Influence of reactive compatibilization on the structure and properties of PP/LDH nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer International, 2011)
Polypropylene (PP)/layered double hydroxide (LDH) nanocomposites were prepared by the direct melt intercalation method usingmaleic anhydride grafted polypropylene (PP-g-MAH) as a reactive compatibilizer. The compatibilization effects provided by PP-g-MAH in different weight fractions and their influence on the structure and properties of the final nanocomposites were investigated. The interactions and structural morphology of the nanocomposites were examined by Fourier transform infrared spectroscopy, X-ray diffraction and transmission electronmicroscopy. Thermal, mechanical and rheological properties of these nanocomposites were investigated as a function of compatibilizer concentration. The detailed morphological and X-ray diffraction results revealed that the degree of LDH dispersion increases as the amount of PP-g-MAH increases. Study of the linear viscoelastic properties showed that the storage modulus G' is very sensitive to the microstructure of the nanocomposite. The thermal properties of the nanocomposites were significantly influenced by the weight fraction of PP-g-MAH due to the shielding and nucleating effect of exfoliated layers. Both the tensile strength and modulus showed substantial improvements with increasing PP-g-MAH content, while the elongation at break substantially decreased, although the presence of PP-gMAH somewhat improves these values. The overall results showed that 10 wt% of compatibilizer is optimum to achieve nanocomposites with better performance. (C) 2011 Society of Chemical Industry
Keywords: compatibilization; layered double hydroxides; Nanocomposites; polypropylene; Rheology; thermomechanical properties

Thermal, mechanical, and rheological characterization of polypropylene/layered double hydroxide nanocomposites - Lonkar, Sunil P.; Therias, Sandrine; Leroux, Fabrice; Gardette, Jean Luc; Singh, Raj Pal (Polymer Engineering and Science, 2012)
Polypropylene (PP)/organomodified layered double hydroxide (LDH) nanocomposites were prepared in order to examine the influence of LDH content on thermal, mechanical, and rheological properties. The nanostructure examinations by X-ray diffraction (XRD) and transmission electron microscopy (TEM) confirmed the exfoliated/intercalated dispersion of LDH. Incorporation of the LDH resulted in a noteworthy improvement in the thermal stability of PP. It was shown that the addition of LDH contributed to the reinforcement effect by increasing the elastic modulus. The mechanical performance, as evaluated by stressstrain curves, reveal that PP/LDH hybrid materials showed significant contribution toward increment in elastic modulus, tensile strength but at the expense of impact strength. The rheological response showed a strong influence of LDH particles on the flow behavior of the PP/LDH melt which resulted in enhancement of storage, loss of moduli, and complex viscosity of nanocomposites. Therefore, the nanocomposites have higher moduli but better processibility compared with pure PP. Overall, the results indicated that the LDH particles in nanometer size might act as potential reinforcing agent for polypropylene. POLYM. ENG. SCI., 52:20062014, 2012. (c) 2012 Society of Plastics Engineers